INCREASING THE ROLE OF LEARNING PORTUGUESE LANGUAGE FOR ESTABLISHING THE NATIONS CHARACTER OF TIMOR LESTE - Agostinho dos Santos Gonçalves (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
The study outlined in this article aimed to describe the increasing the role of learning Portuguese for establishing the national character of Timor Leste. Portuguese language learning in Timor Leste needs to be developed seriously. The learning condition of the language still faces many problems, especially related to the material and the learning process. Therefore, the preparation of teaching materials that are truly functional and make it easier for students to learn the language needs to be developed. This needs to be done to make quality learning outcomes. Through quality Portuguese language learning, students will be able to gain understanding and appreciation of the language culture. Cultural insights will have an impact on the building of student character that is compatible with the culture of the nation of Timor Leste.